The PERFORMANCE Of KERUPUK BAWANG AGROINDUSTRY In BANDARLAMPUNG CITY (CASE STUDY Of ONION CRACKER WINDA PUTRI In BANDARLAMPUNG CITY) - Lutfie Syarief, Ayu Nirmala (FEB - Universitas Lampung, 2022)
The purposes of this research are to analyze :1) the performance of agribusiness system of onion cracker household agroindustry , 2) the production process, added value and income of agroindustry onion cracker 3) marketing of product onion cracker and 4) the role of support services facilities. this research used to case study at onion cracker agroindustry in tanjung senang sub-district bandar lampung city. the research was conducted in january - february 2018 and data analysis used to qualitative and quantitative method. the results showed that the procurement of raw materials had not fulfilled price component. (1) the performance of the agroindustry was not good because it had not fulfilled the flexibility component. (2) the production process is going well and agroindustry revenue was considered good because the value of r/c ratio was > 1 and given added value and income was positive. (3) the marketing strategy of the agroindustry has used the 4p marketing mix component, which is the product, price is good, while for the place and promotion component, it has not been used optimally. the marketing chains consisted of two channels. (4) the provided support services of this agroindustry were bank, information and communication technology, transportation, and market procurement process of raw materials that correspond to six right on (time, place, quality, quantity, type, and price).